The Complementary between Technology and Human Capital in the Early Phase of Industrialization - Raphaël Franck; Oded Galor (Center for Economic Studies and ifo Institute (CESifo), 2015)
The research explores the effect of industrialization on human capital formation. Exploiting exogenous regional variations in the adoption of steam engines across France, the study establishes that in contrast to conventional wisdom that views early industrialization as a predominantly deskilling process, the industrial revolution was conducive for human capital formation, generating broad increases in literacy rates and education attainment.
Keywords: N33; N34; O14; O33; 330; capital-skill complementarity; economic growth; industrialization; human capital; steam engine